FRICTION STIR WELDING THROUGH FABRICATED SETUP BY USING CONVENTIONAL HAND DRILLING MACHINE - Siddiqui, M.A.; Jafri, S.A.H.; Qazzafi, M.; Bakr, Mohd Abu; Deen, Mohd; Afsar, Mohd; Bilal, Mohd (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
The present work is based on the motivation to bring the technique of friction stir welding in workshop level so as to weld metals having low temperature such aluminium, lead, etc. As the friction stir welding is an environment friendly joining process. Through this paper an initiative is taken to introduce this recent technology of friction stir welding in the workshop level because friction stir welding is common to scholars and researchers but an uncommon in general. In the present work, we have fabricated low cost setup of friction stir welding by using conventional hand drilling machine for exploring and sharing such a nice invention and gift to humanity given by The Welding Institute, England. As far as life of welder is concerned, our fabricated setup can heal the wounds of the welders suffering from various diseases. An initiative has been taken to fabricate low cost setup of friction stir welding because the actual machine of friction stir welding is very expensive and costly as well as the experimentation of this technique is also costly because the owners of machine allow to work but on high charges. The experiment was performed on the fabricated setup and the workpiece plates were successfully joined through friction stir welding technique. After successful joining, the workpiece was tested for bending and striking test and it was found that the workpiece was safe after the testing which shows the reliability of joint and opens the door for young minds to work further on this technique in order to make this method more familiar in general.